2016
DOI: 10.1017/cem.2016.372
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort study examining treatments and operative interventions for frostbite in a tertiary care hospital

Abstract: Background: Frostbite is a common yet challenging injury to both diagnose and treat. McCauley's frostbite treatment protocol consists of 12 treatments that might well represent the standard of care. However, its effectiveness in preventing operative intervention has yet to be examined. Our objectives were to characterize frostbite injuries in Eastern Ontario, identify risk factors for deep injuries, and assess the protocol's efficacy in preventing operative outcomes. Methods: This cohort study examined patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
1
8
0
3
Order By: Relevance
“…Although this grouping seems intuitively correct, recent epidemiological studies have classified adults aged 30-49 years as the group at high risk of frostbite [18,24]. Moreover, past research has indicated that males are more frequently affected by cold-induced injuries than females, which is also consistent with our results [10,12,18,25,26]. The incidents reported in these studies are strongly related to these findings, as males constituted a vast majority of subjects.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Although this grouping seems intuitively correct, recent epidemiological studies have classified adults aged 30-49 years as the group at high risk of frostbite [18,24]. Moreover, past research has indicated that males are more frequently affected by cold-induced injuries than females, which is also consistent with our results [10,12,18,25,26]. The incidents reported in these studies are strongly related to these findings, as males constituted a vast majority of subjects.…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with the results obtained by Conway et al [20], who noted that 27% of all frostbite victims in Alaska were alcoholics. Likewise, Fabian et al [12] in a 10-year long retrospective study reported that among the top risk factors for frostbite was alcohol abuse.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations